Plasma concentrations of IL-6, MIP-1β, IP-10, and PTX-3 as predictors of the immunological response to antiretroviral treatment in people with HIV - Mejías-Trueba, Marta; Saborido-Alconchel, Abraham; Serna-Gallego, Ana; Trujillo-Rodríguez, María; Muñoz-Muela, Esperanza; Llaves-Flores, Silvia; Espinosa, Nuria; Roca-Oporto, Cristina; Herrero, Marta; Sotomayor, Cesar; López-Cortes, Luis F. (Frontiers in Immunology, 2024)
Despite effective antiretroviral therapy (ART), 15-30% of people with HIV experience poor CD4+ T-cell recovery, termed immunologic non-responders (INR). This study aims to evaluate whether pre-ART plasma levels of interleukin-6 (IL-6), interferon gamma-induced protein-10 (IP-10), macrophage inflammatory protein-1-β (MIP-1β), and/or pentraxin-3 (PTX-3) could predict subsequent immunologic recovery. Seventy-four participants were enrolled and classified as INR and immunologic responders (IR) based on CD4+/CD8+ ratio increase over 24 months after starting ART. The results showed no significant differences in cytokine levels between INR and IR. Therefore, IL-6, IP-10, MIP-1β, and PTX-3 were unsuitable as predictive markers of poor immune recovery.